H∞ based control of a DC/DC buck converter feeding a constant power load in uncertain DC microgrid system. (October 2020) - Boukerdja, Mahdi; Chouder, Aissa; Hassaine, Linda; Bouamama, Belkacem Ould; Issa, Walid; Louassaa, Khalil
Abstract: DC microgrids are gaining more and more popularity and are becoming a more viable alternative to AC microgrids (MGs) due to their advantages in terms of simpler power converter stages, flexible control algorithms and the absence of synchronization and reactive power. However, DC-MGs are prone to instability issues associated with the presence of nonlinear loads such as constant power loads (CPL) known by their incremental negative impedance (INI), which may lead to voltage collapse of the main DC Bus. In this paper, H ∞ -based controller of a source side buck converter is designed to avoid the instability issues caused by the load-side converter acting as a CPL. Besides, the proposed controller allows a perfect rejection of all perturbations that may arise from parameter variations, input voltage and CPL current fluctuations. The design process of H ∞ -based controller is based on the Golver Doyle Optimization Algorithm (GDOA), which requires an augmented system extracted from the small-signal model of the DC/DC converter including the mathematical model of parameter variations and overall external perturbations. The​ H ∞ based controller involves the use of weight functions in order to get the desired performances. The proposed controller is easy to implement and lead to reducing the implementation cost and avoid the use of current measurement that may have some disadvantages. The derived controller is validated by simulation performed in Psim software and experimental setup. Highlights: Constant power load and overall disturbances lead to lose the system performances. System modeling considers the uncertain parameters and whole disturbances. H ∞ controller enables mitigating the constant power load and disturbances effects.